Classical and modern direction-of-arrival estimation - Friedlander, Benjamin (Academic, 2009)
Brings together in one book classical and modern DOA techniques, showing the connections between themContains contributions from the leading people in the fieldGives a concise and easy- to- read introduction to the classical techniquesEvaluates the strengths and weaknesses of key super-resolution techniquesIncludes applications to sensor networks Classical and Modern Direction of Arrival Estimation contains both theory and practice of direction finding by the leading researchers in the field. This unique blend of techniques used in comme.
Keywords: Radio direction finders.; Signal processing.; Electronics in navigation.; elektronické knihy; electronic books